Indonesia’s Emerging Muslim Feminism: Women Leaders on Equality, Inheritance and Other Gender Issues - Feillard, Andrée (Studia Islamika, 1997)
In this article, whose title means "Muslim feminism emerging in Indonesia: women leaders about the similarities, inheritance, and other gender issues", In this article the author presents and discusses a number of Indonesian Muslim women on various issues concerning gender, or relations and the division of roles between women and men in social life.DOI: 10.15408/sdi.v4i1.787